Long Non-coding RNA LINC00941 as a Potential Biomarker Promotes the Proliferation and Metastasis of Gastric Cancer - Liu, Haiming; Wu, Nan; Zhang, Zhe; Zhong, XiaoDan; Zhang, Hao; Guo, Hao; Nie, Yongzhan; Liu, Yuanning (Frontiers in Genetics, 2019)
Gastric cancer (GC) is a considerable global health burden. Accumulating evidence suggests that long noncoding RNAs (lncRNAs) are aberrantly expressed in many cancers and play important roles in GC. However, only a few lncRNAs have been functionally characterized. In this study, we identified that Long Intergenic Non-Protein Coding RNA 941 (LINC00941) is a potential biomarker for diagnosis and prognosis from The Cancer Genome Atlas (TCGA), and we found that the expression of LINC00941 is associated with tumor depth and distant metastasis in GC. Furthermore, functional enrichment analysis of LINC00941 co-expression network demonstrated that LINC00941 might be an essential regulator of tumor metastasis and cancer cell proliferation. To validate our findings, we utilized the loss-of-function analysis to reveal the biological function of LINC00941 in GC cells. Loss-of-function analysis revealed that silence of LINC00941 inhibits GC cells proliferation, migration, and invasion in vitro and modulates tumor growth in vivo. Our findings confirmed that LINC00941 plays an important oncogenic function in GC and may serve as a potential biomarker for diagnosis and prognosis of GC.